Evaluasi Program Pupuk Bersubsidi di Desa Batumanumpak Kecamatan Nassau Kabupaten Toba - Sipahutar, Rogoklas Patulus; Sihombing, Sally Marisa (Universitas Pahlawan Tuanku Tambusai, 2024)
The Subsidized Fertilizer Policy is a strategic policy to encourage increased production and productivity in the Agricultural Sector, where this policy is expected to be able to meet farmers' needs for the amount of fertilizer needed. However, the implementation of this subsidized fertilizer policy in Batumanumpak Village is still faced with problems or inconsistencies in the distribution of fertilizer with the applicable policies. So an assessment/evaluation of policies related to subsidized fertilizer in Batumanumpak Village is needed.This research aims to evaluate the subsidized fertilizer program in Batumanumpak Village, Nassau District, Toba Regency. The method used is a descriptive qualitative research method with data collection techniques, namely interviews, observation and documentation. The theory used is William N. Dunn's (2003:429) Evaluation theory with indicators, namely: effectiveness, efficiency, adequacy, alignment, responsiveness, accuracy.The research results for the effectiveness dimension have not gone well, because the goals set have not been achieved. The efficiency dimension has also not been implemented well, due to differences in HET and non-compliance with the specified time. The sufficiency dimension is also not working well because the amount of fertilizer released cannot meet the needs of the community. The leveling dimension has been implemented well, and the responsiveness dimension has not been implemented well, because the local government has not fully listened to the community's complaints and has not been able to provide solutions.